Jón Leifs and the musical invention of Iceland - Árni Heimir Ingólfsson (Music, nature, place., 2019)
In Jón Leifs and the Musical Invention of Iceland, Árni Heimir Ingólfsson provides a striking account of the dramatic career of Iceland's iconic composer. Leifs (1899-1968) was the first Icelander to devote himself fully to composition and this book enriches our appreciation of his music by exploring the political, literary and environmental contexts that influenced his work.